Improvements in rate of development and magnitude of force with intense auditory stimuli in patients with Parkinson's disease. - Anzak, A; Tan, H; Pogosyan, A; Djamshidian, A; Ling, H; Lees, A; Brown, P (2011)
Patients with Parkinson's disease can show brief but dramatic normalization of motor activity in highly arousing situations, a phenomenon often termed paradoxical kinesis. We sought to mimic this in a controlled experimental environment. Nine patients with Parkinson's disease and nine age-matched healthy controls were asked to grip a force dynamometer as quickly and strongly as possible in response to a visual cue. A loud (96 dB) auditory stimulus was delivered at the same time as the visual cue in ~50% of randomly selected trials. In patients with Parkinson's disease, the experiment was conducted after overnight withdrawal of antiparkinsonian drugs and again 1 h after patients had taken their usual morning medication. Patients showed improvements in the peak rate of force development and the magnitude of force developed when loud auditory stimuli accompanied visual cues. Equally, they showed improvements in the times taken to reach the peak rate of force development and their maximal force. The paradoxical facilitatory effect of sound was similar whether patients were off or on their usual antiparkinsonian medication, and could be reproduced in age-matched healthy controls. We conclude that motor improvement induced by loud auditory stimuli in Parkinson's disease is related to a physiological phenomenon which survives both with and after withdrawal of antiparkinsonian medication. The potential independence of the mediating pathways from the dopaminergic system provides impetus for further investigation as it may yield a novel nondopaminergic target for therapeutic manipulation in Parkinson's disease.